Some studies on somatic embryogenesis : A tool in plant biotechnology - Neumann, Karl-Hermann; Justus Liebig University Giessen (My University, 2000)
Biotechnology is an area of production and research in which biological systems and biological principles are employed to solve technological problems. This includes beer brewing using yeast as well as the production of pharmaceuticals by immobilized enzymes. Also some systems in biotechnology were developed using cultured cells of higher plants to produce economically valuable chemical compounds, mostly of pharmaceutical interests, in fermenter systems up to some ten thousand liters. Still, in spite of great efforts during the last decades only rather few applications of such systems in commercial companies became known. Here economic considerations require that the product for the market should not only have the same price as the conventionally produced one from raw material obtained from agricultural products. In order to initiate a change in the production process the fermenter product has to be at least at halve the production costs as the conventionally produced compound.
Keywords: ddc:570